2018
DOI: 10.1097/mpg.0000000000002033
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Length of Stay and 30‐Day Revisits in Pediatric Acute Pancreatitis

Abstract: Certain demographic and clinical factors, including gender, ethnicity, and type of CCC, were independently associated with LOS and risk of 30-day hospital revisit for pediatric AP. Children with malignant and gastrointestinal CCCs who require total parenteral nutrition are at highest risk for both longer LOS and hospital revisit when admitted with AP. These patient populations may benefit from intensive care coordination when hospitalized for AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…We also found that gender was another a risk factor of length of hospital stay. The female patients stayed longer than male ones (Table 1), and this phenomenon consisted with previous report in pediatric AP patients 4 . After adjustment for severity classi cation and gender, length of hospital stay still positively correlated with MCH (P = 0.000, Table 4).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We also found that gender was another a risk factor of length of hospital stay. The female patients stayed longer than male ones (Table 1), and this phenomenon consisted with previous report in pediatric AP patients 4 . After adjustment for severity classi cation and gender, length of hospital stay still positively correlated with MCH (P = 0.000, Table 4).…”
Section: Discussionsupporting
confidence: 87%
“…The correlation analyses were carried out in all subjects. The basic demographic characteristics, such as gender, age and severity of AP, might in uence length of hospital stay 4 . The laboratory parameters of study participants, such as WBC and HGB, might in uence length of hospital stay as well.…”
Section: The Correlation Analyses In Multiple Linear Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Pohl et al (2015) reported that children with AP are hospitalized for 5-8 days, while infants and toddlers spend approximately 20 days in the hospital [22]. Gay et al showed that the median LOS was four days (interquartile range: 3-7 days) [23]. Pancreatic pseudocysts may occur in approximately 15% of children with AP, and most cases resolve without intervention [24].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing complex clinical conditions, sociodemographic and interventional factors have been associated with increased hospital length of stay (LOS) in pediatric patients who were discharged with diagnosis of AP. This study did not investigate laboratory parameters or the effects of the recommended fluid hydration [12].…”
Section: Introductionmentioning
confidence: 99%